2016
DOI: 10.1108/ijwhm-11-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Presenteeism “on the desk”

Abstract: Purpose -The purpose of this paper is to examine the antecedents and consequences of the phenomenon of presenteeism in the educational sector. Particularly, the authors tested the relationship between excessive work responsibilities, presenteeism, work-to-family conflict and workers' emotional exhaustion. Design/methodology/approach -A self-report questionnaire was administered to 264 teachers in secondary schools. Findings -A subsequent mediation of presenteeism and work-to-family conflict between work respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Thus, the persistent lack of opportunities for recovery experienced by employees working despite feeling ill, due to their obsession with work, is likely to erode their energy and interfere with their ability to comply with duties deriving from their profession and their family context. Early attempts to explore the impact of presenteeism on work–family conflict indicate that this association could undermine the integrity of employees' health and feed into symptoms of emotional exhaustion (Panari & Simbula, ). To our knowledge, the current study represents the first effort to investigate the role of a psychosocial factor (i.e., managerial support) in buffering the inclination to presenteeism displayed by workaholic employees.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the persistent lack of opportunities for recovery experienced by employees working despite feeling ill, due to their obsession with work, is likely to erode their energy and interfere with their ability to comply with duties deriving from their profession and their family context. Early attempts to explore the impact of presenteeism on work–family conflict indicate that this association could undermine the integrity of employees' health and feed into symptoms of emotional exhaustion (Panari & Simbula, ). To our knowledge, the current study represents the first effort to investigate the role of a psychosocial factor (i.e., managerial support) in buffering the inclination to presenteeism displayed by workaholic employees.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional exhaustion is another subjective variable that can occur following a decrease in employees' job satisfaction [ 25 , 26 ]. Emotional exhaustion can also be the result of long-term presenteeism [ 27 ]. In this regard, research studies indicate that presenteeism leads to exhaustion and depersonalization and predicts job absence [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demerouti et al studied nurses and indicated that presenteeism was a dangerous organizational behavior that could lead to long-term burnout [ 29 ]. This was probably because presenteeism does not give individuals a chance to recover, thereby leading to emotional exhaustion in the long term [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using data from self-report questionnaires, the study found workload and student behavior and employment conditions as determinants of depression and anxiety in teachers (Ferguson et al, 2012). Elsewhere, a study by Panari and Simbula (2016) noted the mediating role played by presenteeism on the relationships with work tasks, work-to-family conflict and emotional exhaustion among Italian schoolteachers. Utilizing a self-report questionnaire, the study surveyed 264 secondary school teachers.…”
Section: Mental/emotional Statementioning
confidence: 95%